Assessment of selected angiogenesis markers in the serum of middle‐aged male patients with plaque psoriasis. Issue 1 (6th January 2021) - Socha, Mateusz; Kicinski, Paweł; Feldo, Marcin; Zubilewicz, Tomasz; Pietrzak, Aldona
Abstract: Local angiogenesis accompanies inflammation in psoriasis‐affected skin. To determine the serum concentrations of selected pro‐ and anti‐angiogenic factors and their interrelationships in patients with plaque psoriasis. The study included 41 men diagnosed with psoriasis, aged 43.5 ± 11.7 years. The Psoriasis Area and Severity Index score was 23.4 ± 5.2 points. The control group consisted of 38 healthy, age‐matched men. The levels of pro‐angiogenic cytokines and angiogenesis inhibitors, including fibroblast growth factor 1 (FGF‐1), vascular endothelial growth factor A (VEGF‐A), endostatin, and angiostatin, were determined from the serum of patients and controls using enzyme‐linked immunosorbent assays. Compared with controls, patients with psoriasis had a significantly lower concentration of FGF‐1 ( P = .01) but higher concentrations of endostatin ( P = .04) and angiostatin ( P = .02). The concentration of VEGF‐A was also higher in patients with psoriasis but not significantly ( P = .25). The concentration of C‐reactive protein (CRP) was significantly higher among patients with psoriasis than controls ( P < .0001). Among controls, CRP concentrations did not correlate significantly with the concentrations of FGF‐1, VEGF‐A, endostatin, or angiostatin. Among patients with psoriasis, CRP concentrations correlated moderately with the concentrations of VEGF‐A ( r = .35; P = .02) and angiostatin ( r = .31; P = .04). The concentration of VEGF‐A correlated positively with PASI ( r = .05; P = .0009) and BSA values ( r = .39; P = .01). Psoriasis is associated with an altered systemic balance between pro‐angiogenic and anti‐angiogenic factors. The increase in serum angiogenesis inhibitors may be associated with unfavorable changes in the development of coronary collateral circulation. However, the clinical significance of this has not yet been established.